Spatial analysis of carbon dioxide emission processes from cement production and iron and steel production in Ukraine (Моделювання, керування та інформаційні технології, 2023)
Carbon dioxide is the most significant greenhouse gas with the longest lifespan in the atmosphere. Nowadays it is extremely important to work on finding strategies to reduce carbon dioxide emissions. Due to this, we need to develop advanced monitoring methods that will help us to make better decisions and track both positive and negative trends in carbon dioxide emissions. This study is devoted to spatial analysis of emission processes from cement, iron and steel production in Ukraine.Вуглекислий газ є найважливішим парниковим газом із найдовшим терміном існування в атмосфері. Сьогодні надзвичайно важливо працювати над пошуком стратегій зменшення емісій вуглекислого газу. Тому слід розробити ефективні методи моніторингу, які допоможуть нам приймати кращі рішення та відстежувати як позитивні, так і негативні тенденції у емісіях вуглекислого газу. Це дослідження присвячене просторовому аналізу процесів емісії від виробництва цементу, чавуну та сталі в Україні.